Chelativorans petroleitrophicus sp. nov., a paraffin oil-degrading bacterium isolated from a mixture of oil-based drill cuttings and paddy soil. Issue 3 (31st March 2023) - Yu, Jinyang; Liu, Hanjun; Deng, Yonggang; Penttinen, Petri; Wang, Zuyu; Liu, Yihao; Wang, Yan; Wang, Entao; Sun, Yu; Chen, Keming; Li, Hui; Chen, Liyun; et al.
Abstract : We isolated a paraffin oil-degrading bacterial strain from a mixture of oil-based drill cutting and paddy soil, and characterized the strain using a polyphasic approach. The Gram-positive, aerobic, rod-shaped and non-spore-forming strain (SCAU 2101 T ) grew optimally at 50 °C, pH 7.0 and 0.5 % (w/v) NaCl. Phylogenetic analysis based on 16S rRNA gene sequence indicated that the strain represented a distinct clade in the genus Chelativorans, neighbouring Chelativorans intermedius LMG 28482 T (97.1 %). The genome size and DNA G+C content of the strain were 3 969 430 bp and 63.1 mol%, respectively. Whole genome based phylogenomic analyses showed that the average nucleotide identity and digital DNA–DNA hybridization values between strain SCAU 2101 T and C. intermedius LMG 28482 T were 77.5 and 21.2 %, respectively. The major respiratory quinone was Q-10. The dominant fatty acids were C19 : 0 cyclo ω 8 c (50.6 %), summed feature 8 (C18 : 1 ω 7 c and/or C18 : 1 ω 6 c ; 22.5 %) and C18 : 0 (13.8 %). The polar lipids of the strain included phosphatidylethanolamine, phosphatidylmonomethylethanolamine, phosphatidylglycerol, phosphatidylcholine and diphosphatidylglycerol. Based on the results, strain SCAU 2101 T was considered to represent a novel species in the genus Chelativorans, for which the name Chelativorans petroleitrophicus sp. nov. is proposed. The type strain is SCAU 2101 T (= CCTCC AB 2021125 T =KCTC 92067 T ).